ChemInform Abstract: Synthesis of Novel 2‐Alkyl Triazole‐3‐alkyl Substituted Quinoline Derivatives and Their Cytotoxic Activity. Issue 28 (21st June 2013) - Rao, P. Sambasiva; Kurumurthy, C.; Veeraswamy, B.; Kumar, G. Santhosh; Rao, P. Shanthan; Pamanji, R.; Rao, J. Venkateswara; Narsaiah, B.
Abstract Most of the novel quinoline derivatives (III) (15 examples) show significant cytotoxicity on human cancer cell lines.